Evaluation of the potential coloring and antioxidant of betalains (Beta vulgaris, L.) in chicken mortadella (Research, Society and Development, 2020)
The objective of the research was to extract betalains from beets root and to evaluate their potential as a dye and natural antioxidant in chicken bologna. Through the quantification of betalains by the phonophometric method, you can obtain a better extraction in aqueous, alcoholic, hydroalcoholic solvent in neutral pH and hydroalcoholic in pH 3. The optimized beet extractor was dried at 40 ° C, being analyzed or its theoretical content phenolic. Four mortadella formulations were made: MC (negative control) = addition of 0.05% synthetic dye, MBHT = addition of antioxidant BHT 0.01% and synthetic dye 0.05%, M4% = addition of 4% extract beet; M6% = addition of 6% extract beet. They were performed as lipid oxidation (TBARS), pH, water activity (Aa) and color (a *, L *, b *) analyzes for 45 days, evaluated by linear regression data. It was found that the best solvent was hydroalcoholic at neutral pH, resulting in 153.14 mg / L of betalains and 99.1 mg EAG / g of phenolic compounds. After a period of 45 days, the pH and Aa values did not change, there was an increase in the brightness of MC and M4%, a reduction in the red color by M6%, which suggests the degradation of betacyanins by the antioxidant activity and a decreasing yellow color by M4% and M6%, degradation of betaxanthines. At the end of the study, M4% and M6% had the lowest lipid oxidation values. These results confirmed the potential of betalains as dyes and natural antioxidants